Modified Broström repair with suture tape augmentation for lateral ankle instability: A systematic review. Issue 3 (April 2021) - Lewis, T.L.; Joseph, A.; Patel, A.; Ahluwalia, R.; Ray, R.
Highlights: Ankle instability treated with suture tape has excellent clinical outcomes. No clear difference between Modified Broström and suture tape augmentation. Abstract: Background: There is increasing interest in augmentation of modified Broström repairs for lateral ankle instability with a prosthetic reconstruction using suture tape internal bracing. The aim of this study was to investigate if suture tape augmentation resulted in improved clinical and radiological outcomes compared to a standard modified Broström repair alone. Methods: A systematic review following PRISMA guidelines was undertaken. All clinical studies published in Medline, Embase, Pubmed and the Cochrane Library Database from inception until January 2020 reporting on the use of suture tape augmentation to a modified Broström repair for lateral ankle instability. Results: 78 studies were identified of which 10 (assessing 333 patients) met the criteria for inclusion. Mean follow up was 24.8 months (range 6–52 months). All studies showed a statistically significant improvement across multiple clinical outcome measures post-surgery in both suture tape augmentation and modified Broström groups, however there were no statistically significant inter-group differences. Pooled results suggested there may be a reduction in recurrence of instability with suture tape augmentation when compared to modified Broström repair alone (p < 0.05). Overall quality of evidence was moderate to poor with limited data to support use of suture tape augmentation. Conclusion: Clinical and radiographic outcomes using a suture tape internal bracing for lateral ankle instability are excellent, and are equivalent to standard treatment across multiple clinical and radiographic assessment measures. There is minimal evidence to suggest functional outcomes are better, or recurrence rates are lower than modified Broström repair alone. PROSPERO REGISTRY: CRD42020169876. Level of evidence: II.